Molecular epidemiology of sisal bole rot disease suggests a potential phytosanitary crisis in Brazilian production areas - Raya, Fábio Trigo; Quintanilha-Peixoto, Gabriel; de Oliveira, Adriele Barbara; Marone, Marina Püpke; dos Reis, Wagner José Villela; Marques, João Gabriel Oliveira; Almeida, Rafael Leonardo; Falcão Filho, Cezar Augusto Teixeira; Costa, Oldair Del’Arco Vinhas; Ribeiro, Rafael Vasconcelos; Soares, Ana Cristina Fermino; Goés-Neto, Aristóteles; et al. (Frontiers in Chemical Engineering, 2023)
Sisal bole rot disease is the major phytosanitary problem of Agave plantations in Brazil. The disease is caused by a cryptic species of Aspergillus: A. welwitschiae. To date, the only way to diagnose the disease was to observe external symptoms, visible only when the plant is already compromised, or through the isolation and sequencing of the pathogen, which requires cutting the entire plant for bole tissue sampling. We developed a new primer set based on a unique gene region of A. welwitschiae, which can detect the phytopathogenic strains through PCR directly from sisal leaves. Using the new marker to study the main sisal-producing areas in Brazil, we discovered a troublesome situation. The main producing areas of this crop had a pathogen incidence of 78-88%. The dispersion index indicates a regular spatial pattern for disease distribution, suggesting that the use of contaminated suckers to establish new fields may be the main disease-spreading mechanism. Altogether, the high incidence of the pathogen, the unavailability of clean plants, the unpredictability of disease progression, and the low investment capacity of farmers reveal the vulnerability of this sector to a potential phytosanitary crisis.By correlating the disease symptomatology with soil nutritional traits, we suggest that higher potassium This is a provisional file, not the final typeset article availability might decrease visual symptoms, while phosphorus may have the opposite effect. Also, we observe a potential cultivar effect, suggesting that common sisal may be more susceptible than hybrid cultivars (especially H400). This new molecular tool is a significant advance for understanding the disease, enabling the implementation of a monitoring program and studies that may lead to pathogen control strategies and changes in the Brazilian production model.